Pelaksanaan Supervisi Observasi Kelas Sebagai Upaya Meningkatkan Kinerja Guru Dalam Melaksanakan Pembelajaran yang Efektif Di SMP Negeri 3 Simeulue Timur Tahun 2022 - Ahmadi (Journal of Technology and Literacy in Education, 2022)
The research aims to improve teacher performance in carrying out effective learning through supervision of class observations at SMP Negeri 3 Simeulue Timur in 2022. Six teachers at SMP Negeri 3 Simeulue Timur were taken. The research method used was school action. In this action research carried out in 2 cycles, each cycle consists of the planning stage, the action implementation stage, the observation stage, and the reflection stage. The data collection technique from this school action research is through qualitative data obtained from teacher observations carrying out effective learning. The analysis technique used in this study is to use descriptive qualitative data analysis techniques using the percentage formula. Based on the results of the research that has been carried out, it is known that in cycle I the overall average value obtained is 76% or is in the sufficient criteria. Only 2 teachers got good criteria, while 4 other teachers still got enough criteria. In cycle II, from the observation results, it was known that the overall average value obtained was 88.87% or was in good criteria, and experienced an increase of 12.87% from cycle I. A total of 2 teachers got very good criteria, and 4 teachers other teachers got good criteria. so that it can be concluded that the implementation of classroom observation supervision can improve teacher performance in carrying out effective learning at SMP Negeri 3 Simeulue Timur in 2022.